Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To expand the expression [tex]\((-x - 3)^5\)[/tex], we need to apply the binomial theorem, which states:
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^{k} \][/tex]
In this case, [tex]\( a = -x \)[/tex] and [tex]\( b = -3 \)[/tex], and [tex]\( n = 5 \)[/tex]. Using the binomial expansion, we have:
[tex]\[ (-x - 3)^5 = \sum_{k=0}^{5} \binom{5}{k} (-x)^{5-k} (-3)^{k} \][/tex]
Let's break it down step by step:
1. For [tex]\( k = 0 \)[/tex]:
[tex]\[ \binom{5}{0} (-x)^{5-0} (-3)^{0} = 1 \cdot (-x)^5 \cdot 1 = -x^5 \][/tex]
2. For [tex]\( k = 1 \)[/tex]:
[tex]\[ \binom{5}{1} (-x)^{5-1} (-3)^1 = 5 \cdot (-x)^4 \cdot (-3) = 5 \cdot x^4 \cdot (-3) = -15x^4 \][/tex]
3. For [tex]\( k = 2 \)[/tex]:
[tex]\[ \binom{5}{2} (-x)^{5-2} (-3)^2 = 10 \cdot (-x)^3 \cdot 9 = 10 \cdot (-x)^3 \cdot 9 = 10 \cdot -x^3 \cdot 9 = -90x^3 \][/tex]
4. For [tex]\( k = 3 \)[/tex]:
[tex]\[ \binom{5}{3} (-x)^{5-3} (-3)^3 = 10 \cdot (-x)^2 \cdot (-27) = 10 \cdot x^2 \cdot (-27) = -270x^2 \][/tex]
5. For [tex]\( k = 4 \)[/tex]:
[tex]\[ \binom{5}{4} (-x)^{5-4} (-3)^4 = 5 \cdot (-x)^1 \cdot 81 = 5 \cdot -x \cdot 81 = -405x \][/tex]
6. For [tex]\( k = 5 \)[/tex]:
[tex]\[ \binom{5}{5} (-x)^{5-5} (-3)^5 = 1 \cdot x^0 \cdot (-243) = -243 \][/tex]
Now, summing all these terms together:
[tex]\[ -x^5 - 15x^4 - 90x^3 - 270x^2 - 405x - 243 \][/tex]
Thus, the expanded form of [tex]\((-x - 3)^5\)[/tex] is:
[tex]\[ -x^5 - 15x^4 - 90x^3 - 270x^2 - 405x - 243 \][/tex]
So, the correct choice is:
A. [tex]\(-x^5 - 15 x^4 - 90 x^3 - 270 x^2 - 405 x - 243\)[/tex]
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^{k} \][/tex]
In this case, [tex]\( a = -x \)[/tex] and [tex]\( b = -3 \)[/tex], and [tex]\( n = 5 \)[/tex]. Using the binomial expansion, we have:
[tex]\[ (-x - 3)^5 = \sum_{k=0}^{5} \binom{5}{k} (-x)^{5-k} (-3)^{k} \][/tex]
Let's break it down step by step:
1. For [tex]\( k = 0 \)[/tex]:
[tex]\[ \binom{5}{0} (-x)^{5-0} (-3)^{0} = 1 \cdot (-x)^5 \cdot 1 = -x^5 \][/tex]
2. For [tex]\( k = 1 \)[/tex]:
[tex]\[ \binom{5}{1} (-x)^{5-1} (-3)^1 = 5 \cdot (-x)^4 \cdot (-3) = 5 \cdot x^4 \cdot (-3) = -15x^4 \][/tex]
3. For [tex]\( k = 2 \)[/tex]:
[tex]\[ \binom{5}{2} (-x)^{5-2} (-3)^2 = 10 \cdot (-x)^3 \cdot 9 = 10 \cdot (-x)^3 \cdot 9 = 10 \cdot -x^3 \cdot 9 = -90x^3 \][/tex]
4. For [tex]\( k = 3 \)[/tex]:
[tex]\[ \binom{5}{3} (-x)^{5-3} (-3)^3 = 10 \cdot (-x)^2 \cdot (-27) = 10 \cdot x^2 \cdot (-27) = -270x^2 \][/tex]
5. For [tex]\( k = 4 \)[/tex]:
[tex]\[ \binom{5}{4} (-x)^{5-4} (-3)^4 = 5 \cdot (-x)^1 \cdot 81 = 5 \cdot -x \cdot 81 = -405x \][/tex]
6. For [tex]\( k = 5 \)[/tex]:
[tex]\[ \binom{5}{5} (-x)^{5-5} (-3)^5 = 1 \cdot x^0 \cdot (-243) = -243 \][/tex]
Now, summing all these terms together:
[tex]\[ -x^5 - 15x^4 - 90x^3 - 270x^2 - 405x - 243 \][/tex]
Thus, the expanded form of [tex]\((-x - 3)^5\)[/tex] is:
[tex]\[ -x^5 - 15x^4 - 90x^3 - 270x^2 - 405x - 243 \][/tex]
So, the correct choice is:
A. [tex]\(-x^5 - 15 x^4 - 90 x^3 - 270 x^2 - 405 x - 243\)[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.